Frequent transmission of the Mycobacterium tuberculosis Beijing lineage and positive selection for the EsxW Beijing variant in Vietnam - Holt, K; McAdam, P; Thai, P; Thuong, N; Ha, D; Lan, N; Lan, N; Nhu, N; Hai, H; Ha, V; Thwaites, G; Edwards, D; et al. (Nature Publishing Group, 2018)
To examine transmission dynamics of Mtb isolated from TB patients in Ho Chi Minh City, Vietnam we sequenced whole genomes of 1,635 isolates and compared these with 3,144 isolates from elsewhere. The data reveal an underlying burden of disease caused by endemic Mtb Lineage 1 associated with activation of long-term latent infection, and a three-fold higher burden associated with more recently introduced Beijing lineage and Lineage 4 Mtb strains. We find that Beijing lineage Mtb is frequently transferred between Vietnam and other countries, and detect higher levels of transmission of Beijing lineage strains within this host population than endemic Lineage 1 Mtb. Screening for parallel evolution of Beijing lineage-associated SNPs in other Mtb lineages as a signal of positive selection, we identify a mutation in the ESX-5 type VII secreted protein EsxW, which could potentially contribute to the enhanced transmission of Beijing lineage Mtb in Vietnamese and other host populations.